Design safety margin of a 10, 000 TEU container ship through ultimate hull girder load combination analysis. (March 2016) - Alfred Mohammed, E.; Benson, S.D.; Hirdaris, S.E.; Dow, R.S.
Abstract: Assessment of the ultimate longitudinal strength of hull girders under combined waveloads can be of particular importance especially for ships with large deck openings and low torsional rigidity. In such cases the horizontal and torsional moments may approach or exceed the vertical bending moment when a vessel progresses in oblique seas. This paper presents a direct calculation methodology for the evaluation of the ultimate strength of a 10, 000 TEU container ship by considering the combined effects of structural non-linearities and steady state wave induced dynamic loads on a mid ship section cargo hold. The strength is evaluated deterministically using non-linear nite element analysis. The design extreme values of principal global wave-induced load components and their combinations in irregular seaways are predicted using a cross-spectral method together with short-term and long-term statistical formulations. Consequently, the margin of safety between the ultimate capacity and the maximum expected moment is established. Highlights: A finite element model was developed for three compartments of a 10, 000 TEU container ship. Combined ultimate strength analyses under vertical bending and torsional moments were performed. An interaction curve between vertical bending and torsional moments was developed. A design extreme value of vertical bending moment and its associated torsional moment was obtained. A margin of safety under combined loads was determined using results from the last two steps above.